2019
DOI: 10.1111/jav.01972
|View full text |Cite
|
Sign up to set email alerts
|

Flight activity in pallid swiftsApus pallidusduring the non‐breeding period

Abstract: Flight activity recorders have recently confirmed that alpine and common swifts spend the majority of their non‐breeding period on the wing, which may last 6–10 months. Here we test the hypothesis that the closely related pallid swift, a species with a breeding distribution around the Mediterranean, lead a similar aerial life‐style during its migration and wintering periods. The pallid swift usually lays two clutches in one season and therefore spends more time in the breeding area than the common swift. We su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…This temporal strategy may make them vulnerable to unusually dry years when late rains and insect concentrations do not occur (Boano and Bonardi 2005). Pallid swifts are mainly aerial outside the breeding season and given the large movements within the sub-Saharan non-breeding range documented here, they seem predisposed to opportunistically respond to variation in prey availability between and within years (Hedenström et al 2019). However, another common nonbreeding visitor south of the Sahara from the temperate zone, the common swift, winters further south in Africa in areas where the general timing of the birds in relation to the rainy season may differ from that in the Sahel (Åkesson et al 2012, 2016).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…This temporal strategy may make them vulnerable to unusually dry years when late rains and insect concentrations do not occur (Boano and Bonardi 2005). Pallid swifts are mainly aerial outside the breeding season and given the large movements within the sub-Saharan non-breeding range documented here, they seem predisposed to opportunistically respond to variation in prey availability between and within years (Hedenström et al 2019). However, another common nonbreeding visitor south of the Sahara from the temperate zone, the common swift, winters further south in Africa in areas where the general timing of the birds in relation to the rainy season may differ from that in the Sahel (Åkesson et al 2012, 2016).…”
Section: Discussionmentioning
confidence: 76%
“…Similar to the closely related common swift A. apus (Pellegrino et al 2017), the pallid swift show general morphological modifications to an aerial life-style, such as high aspect ratio wings, a streamlined body and an energy efficient flight style (Hedenström et al 2016, Sachs 2017. It was recently also empirically shown that pallid swifts mainly spend the non-breeding season on the wings (Hedenström et al 2019), something earlier described in alpine swifts Tachymarptis melba (Liechti et al 2013) and common swifts (Hedenström et al 2016). Despite their energy-saving modifications, swifts are still likely facing higher daily energetic costs relative to other species with a more terrestrial life-style due to the elevated expenditure related to flapping flight (Norberg 1990).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations